2016
DOI: 10.14745/ccdr.v42i01a03
|View full text |Cite
|
Sign up to set email alerts
|

CATMAT statement on disseminated strongyloidiasis: Prevention, assessment and management guidelines

Abstract: Background: Strongyloides stercoralis is a parasitic nematode found in humans, with a higher prevalence in tropical and sub-tropical regions worldwide. If untreated, the infection can progress to disseminated strongyloidiasis, a critical illness which may be fatal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
118
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(134 citation statements)
references
References 25 publications
0
118
0
16
Order By: Relevance
“…Strongyloides infections can disseminate following immunosuppression and cause a severe and frequently fatal disease [94]. Screening for Strongyloides is now recommended prior to initiating immunosuppressive medications in patients who have spent significant time in endemic countries [95]. Similarly, neurocysticercosis should be considered in those with seizure disorders from endemic countries, even if they have not visited an endemic region in many years.…”
Section: Clinical Implications Of Infections Transmitted Via Air Travelmentioning
confidence: 99%
“…Strongyloides infections can disseminate following immunosuppression and cause a severe and frequently fatal disease [94]. Screening for Strongyloides is now recommended prior to initiating immunosuppressive medications in patients who have spent significant time in endemic countries [95]. Similarly, neurocysticercosis should be considered in those with seizure disorders from endemic countries, even if they have not visited an endemic region in many years.…”
Section: Clinical Implications Of Infections Transmitted Via Air Travelmentioning
confidence: 99%
“…No studies describing empiric prophylaxis for Strongyloides were identified in our review. Several organisations including the Brazilian Society of Rheumatology, the Centres for Disease Control and Prevention and the Canadian Committee to Advise on Tropical Medicine and Travel recommend screening and considering empiric prophylaxis prior to immunosuppressive therapy for patients residing in endemic areas or returned travellers with potential Strongyloides exposure . This is particularity relevant if there are clinical manifestations such as unexplained eosinophilia, urticarial or serpiginous skin lesions, pulmonary or gastrointestinal symptoms, or if additional corticosteroids or other immunosuppressive agents are indicated urgently.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative to ivermectin is albendazole; however, efficacy may be lower for this agent 16. In patients with disseminated infection, treatment guidelines recommend prolonged courses of ivermectin alone17 or in conjunction with albendazole18 until symptoms resolve and serial stool examinations return negative. In immunocompromised hosts, treatment may require prolonged courses of ivermectin 12 19.…”
Section: Discussionmentioning
confidence: 99%